"A Better Picture ….". Issue 2 (30th November 2021) - Schwartz, Stephen P.
Abstract: Saul Kripke states in Naming and Necessity that he presents a better picture of the reference of names than the traditional description theory. I answer the question why his picture is better than the traditional description theory.